Moringa oleifera Lam flour biscuits.: a possibility of child supplement (Research, Society and Development, 2022)
The Moringa oleifera (Mo) is a perennial species, of the family Moringaceae, originating in the Himalayas. It is full of benefits to human health, as it helps in the prevention and fight of various diseases, including iron deficiency anemia in children. Interest in this plant and its benefits has increased, many scientists study its nutritional and medicinal properties. Based on these statements, this work aimed to produce Mo flour (leaf powder) and biscuits with the partial replacement of conventional flours, as well as the evaluation of chemical compositions, sensory and acceptability analyses, as well as the possible use of biscuit as a food supplement for children. The study was divided into five stages: flour preparation; preparation of the biscuit; bromatological analysis; sensory analysis and acceptability test and statistical analysis. The values found are arranged and presented in tables and graphs detailing in detail for a better evaluation, among which vitamin C and iron stand out. The biscuits showed high acceptability, so the Mo flour and biscuits can be considered good sources of proteins, carbohydrates, lipids, fibers, vitamin C, and iron, an alternative supplement in food preparations.